Perspective of Soy Formula and Fiber intake among Non-Cow’s Milk Drinker Pediatric Patients; A Survey among Indonesian Health Care Practitioners - Ray Wagiu Basrowi; Erika Wasito; Tonny Sundjaya (World Nutrition Journal, 2020)
Indonesia is one of the highest countries for soy-based product consumption, which the usage also started from early age as breastmilk substitute product, although local regulation and guideline stated that soy-based formula recommended for cow’s milk protein allergy. However, evidences showed that soy-based formula supplemented with fiber in non-cow’s milk drinker could also have health effect to gastrointestinal system. This online survey aimed to explore the perspective of health care practitioners (HCPs) in recommending soy-based formula for non-cow’s milk drinker pediatric patients, as well as identify the required additional ingredient or supplementation, specifically on fiber, in soy-based formula. Majority of respondents (97% of paediatricians (P < 0.001)), (96% of nurses  (P = 0.003)), (99% of midwives (P < 0.001)) recommended soy-based formula as nutritional product toward non-cow’s milk drinker patients. On the added ingredients required, 43% of respondents mentioned that AA and DHA and 31% mentioned that fibre is the ingredient that need to be added to complete the benefits of soy formula. This study concluded that the overall perspective of HCPs showed that soy-based formula is a nutritional product recommended for non-cow’s milk pediatric patients. However, fiber is required to be added to achieve the potential benefits of soy-based formula.